The co-creative responsibility of the engineer (2021)
The human being, created as an image and resemblance from the almighty creator himself, is a natural born engineer, and this constitutes a vital part of his heritage. The creation as a dynamic action promotes and vitalizes the relationship that the human being keeps with the nature and in general with the world he lives in. This is the true mission of men as a co-creator. Engineering, beyond being a tool for man to dominate and to be up above his natural surrounding environment, is a gift that has been given to serve with solidarity as a responsible instrument in the co-creation of the wonderful masterpiece God develops with his sons in the world.